2005
DOI: 10.1002/cncr.21382
|View full text |Cite
|
Sign up to set email alerts
|

Well differentiated thyroid carcinoma is associated with human lymphocyte antigen D‐related 11 in Eastern Hungarians

Abstract: BACKGROUND. Using serologic human lymphocyte antigen (HLA) typing, the authors previously described a strong association between well differentiated thyroid carcinoma and HLA D-related 1 (HLA-DR1) in a population of unselected patients from Eastern Hungary. METHODS. In the current study, the authors used polymerase chain reaction-single strand conformational polymorphism to determine the HLA-DR type in 75 patients with well differentiated thyroid carcinoma from the same area as their previous population, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 41 publications
(49 reference statements)
0
21
0
Order By: Relevance
“…The immune system has a complex effect on tumors behavior, limiting its progression or sometimes inducing further tumor growth [6]. In this study we have found an association between HLA-DRB1*04 and papillary thyroid carcinoma in an Iranian population.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…The immune system has a complex effect on tumors behavior, limiting its progression or sometimes inducing further tumor growth [6]. In this study we have found an association between HLA-DRB1*04 and papillary thyroid carcinoma in an Iranian population.…”
Section: Discussionmentioning
confidence: 51%
“…A highly significant association between HLA-DR1 and thyroid carcinoma in an Italian population has been reported [9]. Association between HLA-DR1 and papil- lary thyroid carcinoma has also been reported in Hungarian population [6]. In another study in Spanish population an association has been reported between HLA-DR11 and papillary thyroid carcinoma [6].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…These authors claimed that the inflammation might have been due to local tissue response to the parathyroid adenoma. In other endocrine tumors, the presence, significance, and cause of chronic inflammation were the subject of numerous studies [9][10][11].…”
Section: Introductionmentioning
confidence: 99%